2013
DOI: 10.1002/jgra.50492
|View full text |Cite
|
Sign up to set email alerts
|

The influence of atmospheric tide and planetary wave variability during sudden stratosphere warmings on the low latitude ionosphere

Abstract: [1] Numerical simulations are performed for a sudden stratosphere warming (SSW) under different atmospheric tide and planetary wave forcing conditions to investigate the tidal variability in the mesosphere and lower thermosphere (MLT). The influence of variability of different tides in the MLT on generating perturbations to the low latitude ionosphere is also investigated. Significant changes are found to occur in the migrating semidiurnal solar (SW2) and lunar (M2) tides as well as in the westward propagating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
157
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(175 citation statements)
references
References 41 publications
18
157
0
Order By: Relevance
“…Forbes and Zhang (2012) concluded that changes in the zonal wind in connection with SSW are responsible for the amplification of lunar tide. Pedatella and Liu (2013) investigated importance of planetary wave amplitude and zonal wind for the modification of tides in the MLT region using Whole Atmosphere Community Climate Model (WACCM) simulations, and concluded that changes in the zonal mean atmosphere are the dominant reason for the amplification of the solar and lunar semidiurnal tides. Since the cycle of the lunar age is 29.53 days, the semidiurnal lunar tide has a periodicity of 14.76 days, which is consistent with periodicity observed in our ionospheric data (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Forbes and Zhang (2012) concluded that changes in the zonal wind in connection with SSW are responsible for the amplification of lunar tide. Pedatella and Liu (2013) investigated importance of planetary wave amplitude and zonal wind for the modification of tides in the MLT region using Whole Atmosphere Community Climate Model (WACCM) simulations, and concluded that changes in the zonal mean atmosphere are the dominant reason for the amplification of the solar and lunar semidiurnal tides. Since the cycle of the lunar age is 29.53 days, the semidiurnal lunar tide has a periodicity of 14.76 days, which is consistent with periodicity observed in our ionospheric data (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical studies have shown that an amplification occurs in both solar and lunar semidiurnal tides at dynamo-region heights in response to stratospheric sudden warmings (Pedatella et al 2012bPedatella and Liu 2013). Those tidal changes can result from changes in the mean flow (e.g., Stening et al 1997), interaction with planetary waves (e.g., Liu et al 2010;, and changes in the tidal sources (e.g., Goncharenko et al 2012).…”
Section: Stratospheric Sudden Warming Effectmentioning
confidence: 99%
“…Stening (2011Stening ( ), analyzing equatorial data during 1960Stening ( -2009, also noted that not all stratospheric sudden warmings cause a counter electrojet event. A numerical study by Pedatella and Liu (2013) showed that the lunar tidal amplification depends on the phase of the moon relative to the timing of the stratospheric sudden warming. Thus, the magnitude of the lunar tidal amplification is not solely dependent on the magnitude of the stratospheric sudden warming.…”
Section: Stratospheric Sudden Warming Effectmentioning
confidence: 99%
“…If in addition to the increase in temperature the usual wintertime eastward zonal mean zonal wind at 10 hPa and at 60°N reverses its direction, then the event is called major or else minor (Andrews et al 1987). During SSW events, the interaction between enhanced planetary waves and tides and the interaction between tides and modified middle atmosphere modulate the tidal components, which register their signature in the upper atmospheric parameters (Jin et al 2012;Pedatella and Liu 2013;Guharay et al 2014). Also, nonlinear interaction between PWs and tides produces additional waves at the sum and the difference frequencies of the two original waves (Teitelbaum and Vial 1991) which fall mainly in the tidal domain.…”
Section: Introductionmentioning
confidence: 99%